Daclatasvir and asunaprevir improves health‐related quality of life in Japanese patients infected with hepatitis C virus. Issue 3 (14th May 2018) - Ikeda, Hiroki; Watanabe, Tsunamasa; Matsumoto, Nobuyuki; Hiraishi, Tetsuya; Nakano, Hiroyasu; Noguchi, Yohei; Hattori, Nobuhiro; Shigefuku, Ryuta; Yamashita, Masaki; Nakahara, Kazunari; Matsunaga, Kotaro; Okuse, Chiaki; et al.
Abstract : Aims: Interferon‐free direct‐acting antiviral agent (DAA) regimens for chronic hepatitis C virus (HCV) patients have improved their health‐related quality of life (HRQOL). Currently, there are no published data assessing the impact of DAAs regimens without sofosbuvir on HRQOL. The aim of this study was to investigate the improvement of HRQOL in Japanese HCV patients treated with a protease inhibitor and a nonstructural protein 5A inhibitor. Methods and Results: A total of 123 Japanese genotype 1b HCV patients receiving daclatasvir (DCV) and asunaprevir (ASV) for 24 weeks were enrolled. HRQOL was assessed using the Japanese version of the Chronic Liver Disease Questionnaire (CLDQ) at baseline; weeks 4, 12, and 24; and post‐24 weeks. Changes in CLDQ scores were calculated by subtracting the CLDQ score at each time point from the baseline value. Improvement in the mean change of the Japanese version of the CLDQ score became statistically significant as early as week 4 after the initiation of treatment (+9.3%; P < 0.0001) and was sustained during and after DCV/ASV treatment. The changes of CLDQ at posttreatment week 24 in patients with sustained virological responses (SVR) were significantly higher than those in patients without SVR (0.4% and −4.1%, respectively; P < 0.05). Conclusions: This study of DCV/ASV treatment for Japanese HCV patients in a clinical setting demonstrated that HRQOL can improve as early as at the initiation of treatment and can continue during and after treatment, regardless of the classes of DAAs regimens and race. Moreover, SVR are needed to continue HRQOL improvement. Abstract : We assessed health‐related quality of life (HRQOL) for Japanese hepatitis C virus patients receiving daclatasvir /asunaprevir treatment during and after treatment in a clinical setting. This study demonstrated that the HRQOL can improve as early as at initiation of treatment and continue during and after treatment, regardless of the classes of direct‐acting antiviral agents regimens and race. Moreover, sustained virological response are needed to continue HRQOL improvement.